A comparative study on glycerol metabolism to erythritol and citric acid in Yarrowia lipolytica yeast cells. Issue 6 (4th August 2014) - Tomaszewska, Ludwika; Rakicka, Magdalena; Rymowicz, Waldemar; Rywińska, Anita
Abstract Citric acid and erythritol biosynthesis from pure and crude glycerol by three acetate‐negative mutants of Yarrowia lipolytica yeast was investigated in batch cultures in a wide pH range (3.0–6.5). Citric acid biosynthesis was the most effective at pH 5.0–5.5 in the case of Wratislavia 1.31 and Wratislavia AWG7. With a decreasing pH value, the direction of biosynthesis changed into erythritol synthesis accompanied by low production of citric acid. Pathways of glycerol conversion into erythritol and citric acid were investigated in Wratislavia K1 cells. Enzymatic activity was compared in cultures run at pH 3.0 and 4.5, that is, under conditions promoting the production of erythritol and citric acid, respectively. The effect of pH value (3.0 and 4.5) and NaCl presence on the extracellular production and intracellular accumulation of citric acid and erythritol was compared as well. Low pH and NaCl resulted in diminished activity of glycerol kinase, whereas such conditions stimulated the activity of glycerol‐3‐phosphate dehydrogenase. The presence of NaCl strongly influenced enzymes activity – the effective erythritol production was correlated with a high activity of transketolase and erythrose reductase. Therefore, presented results confirmed that transketolase and erythrose reductase are involved in the overproduction of erythritol in the cells of Y. lipolytica yeast.